2014
DOI: 10.5380/rf.v45i2.34676
|View full text |Cite
|
Sign up to set email alerts
|

Diversidade E Guildas De Regeneração De Espécies Arbóreas Na Borda De Uma Floresta Nativa Em Contato Com Plantio De Pínus

Abstract: ResumoO objetivo do presente trabalho foi verificar a influência do efeito borda sobre a diversidade e a participação de diferentes guildas de regeneração em um fragmento florestal nativo em contato com reflorestamento de pínus. Para isso, foram amostrados o estrato arbóreo adulto (DAP -diâmetro à altura do peito ≥ 5 cm) e regenerante (altura maior que 15 cm e DAP < 5 cm) em cinco transeções de 20 x 100 m perpendiculares à borda do fragmento. Cada transeção foi subdividida em cinco subparcelas de 20 x 20 m, de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
0
3
0
3
Order By: Relevance
“…For instance, Mauhs andBackes (2002) andDalla Rosa et al (2015) have found values of 2.90 and 3.16, respectively. The lowest value we have found has probably occurred due to the limiting environmental conditions of the high mountain formation (FRANÇA; STEHMANN, 2004), such as low temperatures and lower incidence of solar radiation, due to which such physiognomy has a low evapotranspirative capacity as well as shallow soils, therefore constituting an ecologically selective environment which has enabled the development of a small number of species and high ecological dominance. Higher dominance has also been confirmed by the low Pielou's equitability value (0.75) and the high NRI value of only 10 species (79.6%).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…For instance, Mauhs andBackes (2002) andDalla Rosa et al (2015) have found values of 2.90 and 3.16, respectively. The lowest value we have found has probably occurred due to the limiting environmental conditions of the high mountain formation (FRANÇA; STEHMANN, 2004), such as low temperatures and lower incidence of solar radiation, due to which such physiognomy has a low evapotranspirative capacity as well as shallow soils, therefore constituting an ecologically selective environment which has enabled the development of a small number of species and high ecological dominance. Higher dominance has also been confirmed by the low Pielou's equitability value (0.75) and the high NRI value of only 10 species (79.6%).…”
Section: Discussionmentioning
confidence: 97%
“…It is a pioneer species that invests in the production of large numbers of propagules being an excellent colonizer, but it has a low competitive capacity due to its high light-requirement (MALUF; WIZENTIER, 1998), which makes its development in the understory difficult, especially regarding this fragment where the mean value of canopy closure is 99.35% (MARCON et al, 2014). It is also worth noting the high richness of the Myrceugenia genus among the species of higher community participation and its presence in all height classes, being considered an important genus in the composition of high mountain forests (FRANÇA;STEHMANN, 2004;MEIRELES et al, 2008). According to Landrum (1981), this genus stands out along the Brazilian plateaus eastern coast at elevations above 900-1,000 m and under a cold and humid climate, which is in accordance with the features we have found.…”
Section: Discussionmentioning
confidence: 99%
“…O estudo foi realizado no Parque Natural Municipal João José Theodoro da Costa Neto -PARNAMUL, situado nas coordenadas geográficas centrais de 27°47'22" de latitude sul e 50°20'43" de longitude oeste, e com altitude média de 950 m. O parque faz divisa com rodovias, plantios de Pinus taeda L. e área urbana e rural. Possui vegetação florestal protegida e em estádio intermediário a avançado de sucessão, conforme observado por Dalla Rosa et al (2015).…”
Section: Methodsunclassified
“…The same goes for areas which need to be restored within exotic tree plantation landscapes (e.g. Zanini & Ganade 2005; Ferreira et al 2012, 2013; Schorn et al 2013; Scariot et al 2014; Dalla Rosa et al 2015; Stedille et al 2018a, 2018b). Therefore, knowing the composition and structure of the tree community together as taxonomic groups (i.e.…”
Section: Introductionmentioning
confidence: 94%